Incidence of Complications of Thyroid Surgery (Medicine Today, 2017)
During the period of July 2009 to June 2012 the study was conducted on 200 cases of thyroid swelling in the Department of ENT and Head- Neck surgery, Rangpur Medical College Hospital, Rangpur. The age range of the study population was from 10 years to 75 years. Female to male ratio was 3.14:1. Diagnosis of all cases was established preoperatively by clinical examination, thyroid function tests, fine needle aspiration cytology (FNAC) and ultrasonogram (USG). Most of the patients were suffering from multinodular goiter. Maximum operations were done in the form of subtotal thyroidectomy followed by hemithyroidectomy. 16.5% patients were developed complications. Postoperative haemorrhage and recurrent laryngeal nerve paralysis (5% each) were the most common complications. Among recurrent laryngeal nerve paralysis (4%) were unilateral and 1% was bilateral paralysis. In the study 1.5% deaths were reported due to massive haemorrhage and respiratory obstruction. Considering the above findings, it is mentionable that complications of thyroid surgery can be minimized by sound knowledge of normal and pathologic anatomy and an unhurried, gentle operation technique.Medicine Today 2016 Vol.28(2): 62-65